Malos hábitos alimentarios y su incidencia en el rendimiento escolar de los estudiantes de la Unidad Educativa David Guevara Naranjo, cantón Babahoyo, Provincia de Los Ríos - Zambrano Franco, Cristian Javier (2020)
Globally there is a struggle to reduce adolescent eating disorders, many studies have shown diseases that are generated from a poor dietary intake, however, are habits that determines the future of human health. The food cultures are diverse, including members of the same family, in the present research, analyzes what food cultures adopting teens general education Basic Education David Guevara Naranjo are also the impact is determined these cultures have in relation to the development of learning skills. The study considered various socio-economic and political aspects that seek to improve the eating habits of learners, as well as programs and activities developed in the school, who have not been effective in meeting its objectives. From a quantitative descriptive study and applied research instruments that identify the food culture of adolescents, a proposal to strengthen the application of good eating habits in students, leading to further studies in education arises.